Analisis Pelayanan Publik di Kabupaten Kutai Kartanegara - Efri Novianto (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2018)
It is the right of every citizen to get good and quality public services. Community satisfaction is an indicator of the success of these public service providers, therefore public service providers should be directed to increasing community satisfaction. This study uses a survey approach. Respondents were 120 people selected by accidental techniques and spread in 6 sub-districts. Based on the results of the study, the average level of compliance of the service units (districts) in Kutai Kartanegara District against the Law on Public Services was only 69.83 (yellow zone) with the medium compliance category. While the level of community satisfaction is -0.43 or less satisfied with the services provided. However, the average IKM is 87.71 with an A title or very good.